Fetal cardiac function in recipient twins undergoing fetoscopic laser ablation of placental anastomoses for Stage IV twin–twin transfusion syndrome. (6th June 2013) - Van Mieghem, T.; Martin, A. M.; Weber, R.; Barrea, C.; Windrim, R.; Hornberger, L. K.; Jaeggi, E.; Ryan, G.
ABSTRACT: Objective: Cardiac dysfunction is common in the recipient fetus of twin–twin transfusion syndrome (TTTS). In this study, we aimed to document the severity of fetal cardiac dysfunction in Stage IV TTTS (fetal hydrops) and assess evolution of cardiac function longitudinally after fetoscopic laser surgery . Methods: We reviewed obstetric ultrasound examination data, pre‐ and postoperative echocardiograms and neonatal outcomes for 22 cases of Stage IV TTTS undergoing fetoscopic laser ablation of placental anastomoses between 1998 and 2011. Myocardial performance index, atrioventricular valve flow patterns, ventricular shortening fraction, ventricular hypertrophy, outflow tract obstruction and venous Doppler waveforms were assessed . Results: Nineteen fetuses (86.4%) had ascites, eight (36.4%) had pleural effusions, nine (40.9%) had a pericardial effusion and 12 (54.5%) had subcutaneous edema at presentation. Preoperatively, cardiac function was grossly abnormal in all. Eight fetuses (36.4%) had functional pulmonary atresia and one (4.5%) had functional aortic atresia. Seventy‐seven percent of recipient fetuses survived until birth. Postoperative echocardiographic follow‐up (mean, 26 days) showed that indices of fetal cardiac function improved considerably, but never completely normalized. Six of the eight fetuses with functional pulmonary atresia (75.0%), as well as the fetus with functional aortic atresia, survived to birth. In all cases, the functional atresia resolved within 48 h of laser ablation therapy and none had structural valve anomalies at birth. All fetal effusions resolved after the laser . Conclusions: Fetoscopic laser ablation of placental anastomoses reverses cardiac dysfunction and valvulopathy, even in the most severe cases of TTTS. However, recovery takes longer than in early stage disease. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd .